Laparoscopic total extraperitoneal (TEP) inguinal hernia repair with preperitoneal closed-suction drainage reduced postoperative complications - Guangbo Wu; Danli Shi; Min Chen; Chihao Zhang; Hongjie Li; Meng Luo; Qiang Fan (BMC Surgery, 2023)
Abstract Background Although laparoscopic total extraperitoneal (TEP) inguinal hernia repair has the advantages of less bleeding, less trauma, less pain, and fast recovery, there are several issues that need to be addressed. This study aims to evaluate the effectiveness of preperitoneal closed‑suction drainage on reducing postoperative complications in TEP inguinal hernia repair. Methods A retrospective analysis of 122 patients who underwent TEP inguinal hernia repair between June 2018 and June 2021 was performed. The patients were divided into the drainage group and the non-drainage group according to whether the drainage tube was placed or not. Clinical data, surgical procedures and outcome of these patients were collected and analyzed to assess the effectiveness of drainage. Results A total of 122 patients undergoing TEP surgery were screened, of which 22 were excluded. Most of the patients were male with right indirect inguinal hernia. There was no difference in the mean length of hospital stay between the two groups. Postoperative pain was alleviated by preperitoneal closed‑suction drainage 24 h after operation (p = 0.03). The rate of complications such as scrotal edema, seroma and urinary retention in the drainage group was significantly lower than that in the non-drainage group (p < 0.05). Multivariate regression analysis showed that drainage was beneficial to reduce postoperative complications (OR, 0.015; 95% CI, 0.002–0.140; p < 0.01). In addition, it was worth noting that in subgroup analysis, patients with hernia sac volume > 10 cm3 might receive more clinical benefits by placing drainage tube. Conclusion In TEP inguinal hernia repair, placing drainage tube is a simple and feasible traditional surgical treatment, which can promote postoperative recovery without increasing the risk of infection, especially in patients with large hernia sac volume.